Long-chain alkenes and alkadienes of eight lichen species collected in Japan. (September 2021) - Ikeda, Masashi A.; Nakamura, Hideto; Sawada, Ken
Abstract: The hydrocarbons of eight lichen species isolated in Japan were analyzed, and diverse mono-, di-, and tri-unsaturated alkenes were detected. The positions of the double bonds of C17 alkadienes (heptadecadiene) and C17 –C20 alkenes were determined by mass spectrometry of their dimethyl disulfide adducts. We found that the six lichens containing green algal photobionts were distinguished by the presence of 1, 8-heptadecadiene, 6, 9-heptadecadiene, and 8- and 7-heptadecenes. On the other hand, 1-octadecene, 4-octadecene, and 5-nonadecene were the major alkene components of the two lichens with cyanobacterial photobionts. These alkadienes and alkenes were present in large quantities in the lichen samples. In particular, 1, 8-heptadecadiene accounted for more than 90% of the total alkenes in all four lichens containing it. Our results provide new insights into the origin of C17 alkadienes and C17 –C20 alkenes in environmental and geological samples, and these alkenes can potentially be applied as lichen biomarkers. Graphical abstract: Lichens produce abundantly C17:2 and C17:1 alkenes. These alkenes were identified as 1, 8-heptadecadienes (C17:2 Δ 1, 8 ), C17:2 Δ 6, 9, C17:1 Δ 7 and C17:1 Δ 8 alkenes. However, several lichens were found to produce no C17 alkadienes but C18 and C19 alkenes prominently. Image 1 Highlights: Eight species of lichen produce abundantly C17 alkadienes and C17 –C20 alkenes. Double bond positions in the alkenes were determined by MS of their DMDS adducts. Several lichens produce mainly 1, 8-heptadecadiene and 6, 9-heptadecadiene. Some lichens are characterized by no C17 alkadienes but abundant C18 –C19 alkenes. The heptadecadienes have potential for being lichen biomarkers in geoscience.